Usability and Internationalization. Global and Local User Interfaces Second International Conference on Usability and Internationalization, UI-HCII 2007, Held as Part of HCI International 2007, Beijing, China, July 22-27, 2007, Proceedings, Part II - Aykin, Nuray (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2007)
The 12th International Conference on Human-Computer Interaction, HCI Inter- tional 2007, was held in Beijing, P.R. China, 22-27 July 2007, jointly with the Symposium on Human Interface (Japan) 2007, the 7th International Conference on Engineering Psychology and Cognitive Ergonomics, the 4th International Conference on Universal Access in Human-Computer Interaction, the 2nd International Conf- ence on Virtual Reality, the 2nd International Conference on Usability and Inter- tionalization, the 2nd International Conference on Online Communities and Social Computing, the 3rd International Conference on Augmented Cognition, and the 1st International Conference on Digital Human Modeling. A total of 3403 individuals from academia, research institutes, industry and g- ernmental agencies from 76 countries submitted contributions, and 1681 papers, judged to be of high scientific quality, were included in the program. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation th- oughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This volume, edited by Nuray Aykin, contains papers in the thematic area of - ability and Internationalization, addressing the following major topics: • Designing Global and Local Products and Services • Enhancing and Personalizing the User Experience.